ETHNIC RELATIONS IN THE NORTHERN CAUCASUS: CONFLICT POTENTIAL - SAVVA, Mikhail (CENTRAL ASIA AND THE CAUCASUS, 2004)
Even though ethnic conflicts in Russia are localized while their nature is growing more specific, they still remain one of the priorities and one of the typical features of Russian society today. At the same time, they are the least studied subject with no developed research methodology of its own. There is no agreement on the key concepts: an ethnic conflict and its derivatives (conflict potential and ethnic tension). This is not a purely academic problem: practical measures, behavior of the law enforcement bodies, and the media depend on how we interpret an ethnic conflict. This is why I deem it necessary to offer my interpretation of the key and related terms. An ethnic conflict is one of the types of social confrontation in which at least one of the sides de-scribes itself as an ethnic community. It was V. Tishkov who first offered this interpretation in Russian academic studies: “By ethnic conflict we mean organized political actions, public movements, mass un-rest, separatist actions and even civil wars in which ethnic communities are involved.”1 This approach differs greatly from how the law enforcement structures in the Northern Caucasus (and, probably, across the country) identify ethnic conflicts: for them an ethnic conflict is a situation in which hostile actions were planned as ethnically oriented from the very beginning (that is, the object of hostile actions was selected because of its ethnic affiliation). In Britain and America such crimes are called “hate crimes.” This approach cannot explain the mechanism of such conflicts: a fight at a local discotheque may develop into wide-scale ethnic pogroms. This approach has narrow forecasting potential and cannot reveal the conflicting level of ethnic relations (to say nothing of distorted crime-related statistics as a whole). I am convinced that to describe any clash as an ethnic conflict it should inflict measurable damage on the sides. In the absence of such damage one can only speak about various levels of ethnic tension.